Novel polarization beam splitter with high fabrication tolerance - Donegan, John (My University, 2018)
A highly fabrication tolerant polarization beam splitter is presented. The fabrication tolerances are relaxed by adjusting two voltages. Experiments show on-chip losses of 3.5 dB and extinction ratio of 15 dB at C-band
CLEO: QELS_Fundamental Science 2018
Keywords: Optoelectronics; Integrated optics devices; Polarization-selective devices